Devotion and dissent in Indian history - Vijaya Ramaswamy (ed.) (Foundation books, 2014)
Papers presented at the international conference on 'Devotion and Dissent in Indian History', held at New Delhi during 11-13 March 2010; hosted by Centre for Historical Studies, Jawaharlal Nehru University.